DETERIMINAN AUDITOR SWITCHING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI ISSI PERIODE 2016-2020 - Hikmatul Aulia; Dwi Marlina Wijayanti (Jurnal Akuntansi Dan Manajemen, 2023)
This study aimed to analyzed the factors that affect auditor switching on manufacturing company in ISSI. The population in this study are companies listed in Indonesia Sharia Stock Index (ISSI) the period 2016 to 2020. The number of manufacturing firm sampled in this study were 37 companies, obtained by purposive sampling method. The data analysis technique used is logistic regeression analysis with the application of SPSS program. Based on the analysis conducted, the result showed that the variables opinion going concern and management change does not affect on auditor switching, while auditor reputation having a significant influence on the company sample to perform the auditor switching.